An introduction to the superunified theory of quantum fields & fundamental interactions (Discoveries in pure mathematics) - Erdeni, Besud Chu (Annals of Mathematics and Physics, 2021)
This is intended to describe the physical Universe as self-excited and self-organized mathematical continuum. There does exist the universal pure (not applied) mathematical machine perceived by the intelligent observers in a capacity of certain material world. In this short article we are able to indicate only some key points of the theory which suggests practically infinite amount of combinatorics.